The bulk of the hematopoietic stem cell population is dispensable for murine steady-state and stress hematopoiesis - Schoedel, Kristina B.; Morcos, Mina N. F.; Zerjatke, Thomas; Roeder, Ingo; Grinenko, Tatyana; Vöhringer, David; Goethert, Joachim R.; Waskow, Claudia; Roers, Axel; Gerbaulet, Alexander (Blood, 2016)
Long term repopulating (LT-) hematopoietic stem cells (HSCs) are the most undifferentiated cells at the top of the hematopoietic hierarchy. The regulation of HSC pool size and its contribution to hematopoiesis are incompletely understood. We depleted hematopoietic stem and progenitor cells (HSPCs) in adult mice in situ and found that LT-HSCs recovered from initially very low levels (< 1%) to below 10% of normal numbers but not more, while progenitor cells substantially recovered shortly after depletion. In spite of the persistent and massive reduction of LT-HSCs, steady-state hematopoiesis was unaffected and residual HSCs remained quiescent. Hematopoietic stress, although reported to recruit quiescent HSCs into cycle, was well tolerated by HSPC-depleted mice and did not induce expansion of the small LT-HSC compartment. Only upon 5-Fluorouracil treatment, HSPC-depleted bone marrow was compromised in re-constituting hematopoiesis, demonstrating that HSCs and early progenitors are crucial to compensate myeloablation. Hence, a contracted HSC compartment cannot recover in situ to its original size and normal steady-state blood cell generation is sustained with less than 10% of normal LT-HSC numbers without increased contribution of the few residual cells.
EVALuna2:25877